Students’ Difficulties in Learning Listening Comprehension Through Online Learning - Elfi Yanti Pangku; Ika Paramitha Lantu (Sintuwu Maroso Journal of English Teaching, 2022)
This research is aimed to find out the factors that cause students’ difficulties during online learning in listening class and learning strategies of students to overcome their difficulties in learning listening comprehension. The sample of the research is twenty one students of Academic Listening class at English Education Study Program that conducted in an online learning. This research is a descriptive qualitative one that uses questionnaires, interviews, and documentation to collect data. The researcher distributed the questionnaire and interview to the students that enrolled in Academic Listening class. After analysing the data, the researcher found that the factors that caused fourth-semester students’ difficulties in learning listening comprehension are problems about the message, speaker, and physical setting. Thus, the learning strategies used by the students in learninglistening comprehension are cognitive, metacognitive, memory, compensation, affective, and social. Then, the implementation of the strategies are trying to remember the words by pronouncing them, translating the sentences into their own language, remembering many vocabularies, guessing the meaning of the new word or connecting it with other words in spoken text, listening to many English songs and watching English videos on You tube, encouraging themselves to do the task and to be active in the class, and talking to their classmates if they have problems in listening class.